HARDWARE-SOFTWARE COMPLEX OF TRANSMISSION PIPELINE ANTICORROSION PROTECTION - Alexey O. KRIVTSOV; Nikolay F. KARNAUKHOV (Advanced Engineering Research, 2010)
A structural construction scheme for the hardware-software control complex of transmission pipeline electrochemical anticorrosion protection equipment is offered. Performance features of the complex under test operation according to the developed algorithms with the use of fuzzy logic methods.